Humanity from African Naissance to Coming Millennia (2001)
Humanity From African Naissance to Coming Millennia arises out of the world's first Dual Congress that was held at Sun City (South Africa) in 1998 that refers to a conjoint, integrated meeting of two international scientific associations, the International Association for the Study of Human Palaeontology - IV Congress - and the International Association of Human Biologists. The volume includes 39 refereed papers covering a wide range of topics, from Human Biology, Human Evolution (Emerging Homo, Evolving Homo, Early Modern Humans), Dating, Taxonomy and Systematics, Diet, Brain Evolution, offering the most recent analyses and interpretations in different areas of evolutionary anthropology.